ENVIRONMENTAL IMPACT ON THE PRODUCTION OF FOOD IN THE WORLD AND IN BRAZIL (Fiep Bulletin - online, 2011)
Only one third of the world population lives in developed countries, but consumes about 85% of total resources produced in the world. This study aimed to relate the tables eating habits of hunger and poverty by linking them with waste, environmental degradation and population health. In relation to food production, there is evidence of the need to improve the effectiveness of the system as a whole. In addition, raising cattle requires the intensive use of vast amounts of land, which is often deprived of their productive capacity. Worldwide, approximately 50% of farmland is to pasture for cattle. The consumption of animal protein is essential for the proper functioning of the human body, but emphasized that it is possible to eat this type of protein in animals more efficient in converting vegetable protein into animal. It is estimated that the annual consumption of food in the world is 375 million tonnes and most of them come from plants. Whereas 10% are consumed fresh and 10% are leaves and stems that are thrown away, has thus a waste of almost 4 million tons of food. The quest for sustainable development represents a major challenge for humanity and in particular to Brazil. The development model has evolved from the extraction and subsistence farming to agribusiness intense exploration, applying modern technologies and occupation of the environment, threatening biodiversity. The issue of food production ahead of environmental pressure is not easily resolved. However, with the use of appropriate technologies and improved production processes, transport and storage of food can reduce environmental pressure and improve the quality of living.
Keywords: food; environmental impact; production